2019
DOI: 10.5897/ajps2019.1911
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical study of medicinal plants in chiro district, West Hararghe, Ethiopia

Abstract: Ethnobotanical study of medicinal plants is inadequate in Ethiopia in general, and in Chiro District in particular. Therefore, this study documents medicinal plant utilization, management and the threats encountered on them. The study was conducted from April 2017 to June 2018. Forty eight informants were purposively selected. Socioeconomic and botanical data were gathered using group discussions, semi-structured interviews, and field observations and analysed using informant consensus factor, preference ranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Of the total 58 NTFPs recorded in the study area, 32 species (55.17%) distributed under 30 genera (54.54%), and 25 families (71.42%) were identified as medicinal plants used for one or several diseases. Medicinal plant species identified in our study showed about 28-35% overlap with previous studies (Reshad et al 2017;Fassil and Gashaw 2019;Assefa et al 2021). The high proportion of plant species used for traditional medicine can be attributed to the greater preference of the local community for traditional medication as their primary healthcare system (Pathy et al 2020).…”
Section: Medicinal Plant Speciessupporting
confidence: 45%
“…Of the total 58 NTFPs recorded in the study area, 32 species (55.17%) distributed under 30 genera (54.54%), and 25 families (71.42%) were identified as medicinal plants used for one or several diseases. Medicinal plant species identified in our study showed about 28-35% overlap with previous studies (Reshad et al 2017;Fassil and Gashaw 2019;Assefa et al 2021). The high proportion of plant species used for traditional medicine can be attributed to the greater preference of the local community for traditional medication as their primary healthcare system (Pathy et al 2020).…”
Section: Medicinal Plant Speciessupporting
confidence: 45%
“…The detailed information of each plant recorded from the included original papers is available in Table 2. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Commonly Used Families and Plant Species…”
Section: Resultsmentioning
confidence: 99%
“…The town is located about 326 km from Addis Ababa, the capital of Ethiopia. The relative location of the Chiro district in west Hararghe, Oromia region is shown in Figure 1 (Amare and Getachew, 2019). According to statistical data from Chiro municipality for 2022, approximately 69,793 people live in the town with an annual population change of about 5%.…”
Section: Methodsmentioning
confidence: 99%